The reliability of cube compressive strength test to monitoring the 7 and 28 day concrete strength - Mohammad Adam, Azman (2012)
Each concrete used for construction purposes must passed several tests set by Jabatan Kerja Raya that has been stated in the Standard Specification for Building Work JKR (2005). One of the mandatory tests is the compression test of concrete. This test is a necessary test to ensure the concrete used has a high quality and reach its maximum strength. The concrete compressive test result normally shows the value of strength which is higher than the actual strength of the concrete. This study was conducted to investigate the reliability of the concrete compression test results in statistical analysis. There are 269 data taken from six construction projects and improvements projects. This data is from G30 and G35 grades of concrete for concrete maturity on 7 days and 28 days. From analysis, it is proved that the strength of concrete received higher than the actual concrete strength with the average difference for the G30 at 7 days and 28 days maturity is 12.52 N/mm 2 and 12.93 N/mm2 respectively. While for the G35, the average difference is 10.94 N/mm2 and 7.17 N/mm2 for 7 days and 28 days concrete maturity. Overall, the reliability of the concrete compressive strength is doubtable and this may be due to several factors such as method of curing, water / cement ratio and method of compaction use.